2016
DOI: 10.1021/acs.orglett.6b03318
|View full text |Cite
|
Sign up to set email alerts
|

Computational Chemistry Driven Solution to Rubriflordilactone B

Abstract: The structure of rubriflordilactone B (2) was determined by X-ray crystallography. However, the NMR data of the synthetic sample did not match those reported for 2. It was then suggested that the original sample contained an additional isomer of different solubility, pseudorubriflordilactone B (3), whose structure remained unknown. From theoretical calculations, reexamination of the NMR data, and biogenetic considerations, it is proposed that 3 should be the 16S,17R isomer of 2.T he Schisandraceae, comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…[ 21,22 ] In lieu of the above mentioned activities, the synthesis of different furanones, their derivatives, and their applications in the area of medicine have drawn considerable attention in recent years. [ 23–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 21,22 ] In lieu of the above mentioned activities, the synthesis of different furanones, their derivatives, and their applications in the area of medicine have drawn considerable attention in recent years. [ 23–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…This route nonetheless delivered 2 , the predicted structure of pseudo ‐rubriflordilactone B. Diyne 8 b was also carried through the sequence, giving the C23 epimer of pseudo ‐rubriflordilactone B, epi ‐2 . Comparison of the NMR spectroscopic data of 2 (and epi ‐2 ) with data from the isolation paper revealed a high level of consistency for the former diastereomer, thus providing strong support for the computationally‐predicted stereochemistry; further communications with the Li group supported this conclusion. [9, 25}…”
Section: Methodsmentioning
confidence: 73%
“…Subsequent computational work by Kaufman and Sarotti suggested that the difference between the two forms of rubriflordilactone B lies at C16 and C17 in the EF rings, leading to the proposal of 2 , dubbed pseudo ‐rubriflordilactone B, as the most likely candidate to fit the NMR data reported in the isolation paper. Herein, we describe our efforts to solve this stereochemical puzzle, first by establishing a robust synthetic route to rubriflordilactone B, and second by modification of this route to access the proposed structure of pseudo ‐rubriflordilactone B.…”
Section: Methodsmentioning
confidence: 96%
“…In the absence of natural material and its optical rotation data, no conclusion could be derived on this anomaly. A tentative structure of pseudo‐rubriflordilactone B was later proposed by Sarotti and co‐workers …”
Section: Total Synthesis Of Furo[32‐b]furanone Natural Productsmentioning
confidence: 87%